Effects of Rho Kinase and Actin Stress Fibers on Sustained Extracellular Signal-Regulated Kinase Activity and Activation of G(1) Phase Cyclin-Dependent Kinases - Roovers, Kristin (American Society for Microbiology, 2003)
We recently reported that Rho kinase is required for sustained ERK signaling and the consequent mid-G(1) phase induction of cyclin D1 in fibroblasts. The results presented here indicate that these Rho kinase effects are mediated by the formation of stress fibers and the consequent clustering of α5β1 integrin. Mechanistically, α5β1 signaling and stress fiber formation allowed for the sustained activation of MEK, and this effect was mediated upstream of Ras-GTP loading. Interestingly, disruption of stress fibers with ML-7 led to G(1) phase arrest while comparable disruption of stress fibers with Y27632 (an inhibitor of Rho kinase) or dominant-negative Rho kinase led to a more rapid progression through G(1) phase. Inhibition of either MLCK or Rho kinase blocked sustained ERK signaling, but only Rho kinase inhibition allowed for the induction of cyclin D1 and activation of cdk4 via Rac/Cdc42. The levels of cyclin E, cdk2, and their major inhibitors, p21(cip1) and p27(kip1), were not affected by inhibition of MLCK or Rho kinase. Overall, our results indicate that Rho kinase-dependent stress fiber formation is required for sustained activation of the MEK/ERK pathway and the mid-G(1) phase induction of cyclin D1, but not for other aspects of cdk4 or cdk2 activation. They also emphasize that G(1) phase cell cycle progression in fibroblasts does not require stress fibers if Rac/Cdc42 signaling is allowed to induce cyclin D1.